Results of nerve reconstructions in treatment of obstetrical brachial plexus injuries - Mencl, Libor; Waldauf, Petr; Haninec, Pavel (Acta neurochirurgica, 2015)
BACKGROUND: The aim of this study was to evaluate the results achieved using various surgical techniques in patients with partial and total obstetrical brachial plexus palsy. METHODS: From 2000 to 2013, 33 patients with obstetrical brachial plexus injury underwent surgery. Twenty had follow-up periods greater than 24 months and met the criteria for inclusion in the study. All patients were evaluated using the Active Movement Scale. RESULTS: The outcomes of different nerve reconstructive procedures including nerve transfers, nerve grafting after neuroma resection and end-to-side neurorrhaphy are presented. The overall success rate in upper plexus birth injury was 80 % in shoulder abduction, 50 % in external rotation and 81.8 % in elbow flexion with median follow-ups of 36 months. Success rate in complete paralysis was 87 % in finger and thumb flexion, 87 % in shoulder abduction and 75 % in elbow flexion; the median follow-up was 46 months. Useful reanimation of the hand was obtained in both patients who underwent end-to-side neurotization. CONCLUSION: Improved function can be obtained in infants with obstetrical brachial plexus injury with early surgical reconstruction.
Keywords: Plastic Surgery Procedures; Female; Infant; Brachial Plexus; výsledek terapie; ženské pohlaví; lidé; Neurosurgical Procedures; Treatment Outcome; zákroky plastické chirurgie; neurochirurgické výkony; plexus brachialis; Nerve Transfer; radikulopatie; Male; kojenec; Birth Injuries; Radiculopathy; nervový transfer; neuropatie brachiálního plexu; mužské pohlaví; Brachial Plexus Neuropathies; porodní poranění novorozence; Humans